2020
DOI: 10.3390/ijms21041305
|View full text |Cite
|
Sign up to set email alerts
|

Differential Secretion of Angiopoietic Factors and Expression of MicroRNA in Umbilical Cord Blood from Healthy Appropriate-For-Gestational-Age Preterm and Term Newborns—in Search of Biomarkers of Angiogenesis-Related Processes in Preterm Birth

Abstract: Objectives: Premature birth, defined as less than 37 weeks gestation, affects approximately 12% of all live births around the world. Advances in neonatal care have resulted in the increased survival of infants born prematurely. Although prematurity is a known risk factor for different cardiovascular diseases, little is known about the pathophysiology of vasculature during premature gestation and angiopoietic factors network during premature birth. Aims: The objective of this study was to determine whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Total RNA isolated from UCB samples was pooled to generate one sample per group for microarray experiment. The procedure was performed according to the manufacturer's protocol, as previously described 21 . Generation of sense strand cDNA from the total RNA and subsequent fragmentation and labelling steps were made using GeneChip™ WT PLUS Reagent Kit (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA isolated from UCB samples was pooled to generate one sample per group for microarray experiment. The procedure was performed according to the manufacturer's protocol, as previously described 21 . Generation of sense strand cDNA from the total RNA and subsequent fragmentation and labelling steps were made using GeneChip™ WT PLUS Reagent Kit (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we have investigated umbilical cord blood (UCB) expression levels of small non-coding RNAs (miRNAs) potentially involved in angiogenesis control in preterm newborns and term neonates 21 . In this study, we aimed to investigate global gene expression in UCB samples from preterm neonates and compare it to term newborns.…”
Section: Introductionmentioning
confidence: 99%
“…59 Prematurity was also associated with hypoproteinemia mediated impaired cardiovascular function and an "anti-angiogenic" status established by the downregulation of proangiogenic factors, angio-MiRs (inter alia MiR-125, MiR-126, MiR-145, MiR-150, or MiR155) and the upregulation of angiostatic factors endostatin and thrombospondin-2. 60,61 Serum proteomics have shown that the state of IUGR alters the expression of proteins such as lysophospholipid acyltransferase MBOAT7, serotransferrins, apolipoprotein E, apolipoprotein A-I, SERPIN1, with a known contribution to CVD pathways such as apoptosis, diabetes, dyslipidemia, inflammation, and arterial hypertension. 62 Concerning IUGR, renin, and angiotensin I levels were significantly elevated as well as systolic blood pressure and prolonged mean left ventricular isovolumic relaxation time.…”
Section: Other Potential Cvd Biomarkersmentioning
confidence: 99%
“…Many angiogenesis related miRNAs, including miR-125, decreased significantly in cord blood miRNAs of preterm infants. This may increase the risk of abnormal development and function of the cardiovascular system after these premature infants reached adulthood ( Gródecka-Szwajkiewicz et al, 2020 ).…”
Section: Mir-125 Family and The Maturation And Aging Of Cardiovascular Systemmentioning
confidence: 99%